Response of leek (Allium porrum L.) to different levels of nitrogen dose under agro-climate conditions of Bosnia and Herzegovina - Lutvija KARIĆ; Smiljka VUKAŠINOVIĆ; Dragan ŽNIDARČIČ (Acta Agriculturae Slovenica, 2005)
Field experiment was conducted to evaluate growth, yield and quality of leek (Allium porrum L.) under different nitrogen levels, on a heavy clay loam soil in the agro-climate of central Bosnia and Herzegovina. Treatments comprised four nitrogen levels (0, 50, 100 and 200 kg ha-1), using local leek variety Karentan. The levels of 100 and 200 kg ha-1 were repeated in split applications. Results demonstrated that increasing level of nitrogen to 200 kg ha-1 resulted in greater number of leaves per plant (14.4), maximum  leaves weight (194.6 g   plant-1), higher pseudo-stem diameter (36.3 mm), maximum pseudo-stem weight (146.5 g) and highest total yield (91.98 t ha-1). There was a linear increase in total yield from nitrogen fertilization (r2 = 0.87). There was also slight evidence that higher nitrogen amount decrease dry matter. Furthermore, increase in nitrogen levels had no appreciable effect on chemical composition (total and reducing sugars, vitamin C) of leek.